Doubting and Believing: The Hermeneutics of Suspicion in Contexts of Faith - C. Jan Swearingen (Journal of the Assembly for Expanded Perspectives on Learning, 1997)
A belief-centered pedagogy helps students infuse cultural values into adversarial modes of academic writing.